Feedback-induced nonlinear spin dynamics in an inhomogeneous magnetic field - Tishuo Wang; Zhihuang Luo; Shizhong Zhang; Zhenhua Yu (Communications Physics)
Abstract Nonlinear spin dynamics is essential for predicting complex behaviors of spin systems and has a wide range of applications in physics. Although spin systems have been extensively studied, many intricate behaviors such as self-organizing or chaotic oscillations still need to be better understood with a thorough analysis of nonlinear dynamics. Here we investigate the coupled dynamics of a collection of spins with multiple Larmor frequencies for modeling an inhomogeneous magnetic field and reveal that the nonlinearity induced by a feedback scheme leads to much richer stable dynamic phases, including quasi-periodic orbits and chaos besides the usual limit cycles. We further discuss the robustness of these dynamical phases against experimental noises and the feasibility of realization in various spin systems. Our findings contribute to future observation of nonlinear dynamical phases and prospective applications in spin masers, time crystals and quasi-crystals, and precision measurement.